EFEKTIVITAS PENYEMBUHAN LUKA SAYAT MENGGUNAKAN SALEP EKSTRAK ETANOL DAUN SENGGANI (Melastoma malabathricum L.) PADA KELINCI - Vera Estefania Kaban; Jessi Octavia Aritonang; Yulia Citra Hasibuan; Dian Ika Perbina Meliala (Jurnal Penelitian Farmasi & Herbal, 2020)
Senggani plants also have a reddish purple flower, ripe fruit will break the color purple and reddish brown beans. However, the utilization of senggani leaves is still not getting attention, therefore, to increase the economic value and utilization of this plant, senggani leaf can be formulated in the extract ointment of senggani leaf ethanol to healing the cut on the rabbit so it is expected to give healing effect on the rabbit wound.The purpose of this research is to know the concentration of ethanol extract of senggani leaf in the formulation of the ointment which is most effective in healing the rabbit wound in rabbit and to know the ointment ratio of ethanol extract of senggani leaves with betadine ointment .The samples in this study were extract from senggani leaf extracted by maceration using 80% ethanol solvent and formulated in ointment preparation using ingredients of adeps lanae and vaseline album. All data were tested statistically using ANOVA ONE WAY.Preparation of ointment extract of ethanol senggani leaf can accelerate the healing process of the wound and the most effective is the syrup leaf extract of 50% with an average healing for 11 days while betadine ointment does not experience healing until day 14.Indicating differences between treatment groups were more effective in healing of cuts on rabbits and 50% extracts of ethanol extracts of senggani leaf were more effective than with betadine ointment.